Art Criticism in Argentina - Organizational Aspects of Art - Theory of Institutions : XIII Congress of the International Association of Art Critics. - Fevre, Fermin; Glusberg, Jorge; Safons, Horacio (Buenos Aires : AICA / Argentine Association of Art Critics, 1978)
Audivert, Eduardo ; Bedel, Jacques ; Benedit, Luis Fernando ; Camporeale, Sergio ; Demirjian, Jorge ; Esteves, Mercedes ; Grippo, Victor ; Heredia, Alberto ; Lamelas, David ; Lublin, Léa ; Maler, Leopoldo ; Maler, Vicente ; Marotta, Vicente ; Messil, Gabriel ; Minujin, Marta ; Mir, Jorge Gonzalez ; Obelar, Pablo ; Orensanz, Marie ; Paksa, Margarita ; Pazos, Luis ; Porter, Liliana ; Portillos, Alfredo ; Romberg, Osvaldo ; Testa, Clorindo ; Vinoly, Rafael ; Zelaya, Daniel
Engels
boek